Efficient-and-Stable CH4 Reforming with Integrated CO2 Capture and Utilization using Li4SiO4 Sorbent - Lv, Zongze; Qin, Changlei; Chen, Shuzhen; Hanak, Dawid P.; Wu, Chunfei (Elsevier, 2021)
CO2 capture and utilization has been considered as an up-and-coming short- to mid-term approach to mitigate the excessive CO2 emission. Comparing to the conventional separate capture, transportation and conversion arrangement, the integrated CO2 capture and utilization (ICCU) could largely simplify the complex process and reduce the energy consumption. However, the poor stability of high-temperature CO2 sorption/desorption severely limit the potential of ICCU. Therefore, it is indispensable to develop a new sorbent/catalyst system ensuring the high-efficiency and long-term operation of the ICCU. In this paper, we propose and demonstrate the feasibility and performance of using K2CO3-doped Li4SiO4 as an efficient CO2 sorbent for ICCU operating at a relatively low temperature by dry reforming of methane. Results show that the ratio of H2/CO produced is stabilized at 1±0.05 in the pre-breakthrough stage, and the duration extends to be 1.6 times of the original value in the cyclic operations, displaying an excellent performance in reaction matching and process stability.
Keywords: Integrated CO2 capture and utilization; Li4SiO4-based sorbent; CO2 sorption and desorption; Dry reforming of methane